GC-MS analysis and memory-enhancing effect of hydroalcoholic extract of a polyherbal Unani formulation ‘Majoon Vaj’ in scopolamine- and diazepam-induced amnesic mice (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Majoon (M) Vaj is a polyherbal Unani formulation possessing multiple neuropharmacological activities. It is used to treat Nisyān (dementia) for centuries. It has been reported as improving memory and overall mental faculties. The current study was carried out to assess the nootropic and anti-amnesic activity of M. Vaj in mice to validate its use in Unani medicine. The exteroceptive behavior model elevated plus maze (EPM) and morris water maze (MWM) and interoceptive behavior model (scopolamine and diazepam) were used to evaluate nootropic activity in mice. Pre-treatment with M. Vaj extract (220 and 440 mg/kg, p.o.) for 15 days showed a significant decrease transfer latency (TL) in EPM and decrease escape latency (EL) during training and increase time spent in the target quadrant (TSTQ) during retrieval in the MWM test, indicating nootropic activity. M. Vaj also significantly reversed scopolamine and diazepam-induced amnesia, as observed by decreased TL in EPM and increased TSQT in MWM, indicating anti-amnesic activity. Also, both doses of the test drug showed a similar response, which was almost equal to that of the standard drug piracetam. Reversal of scopolamine and diazepam-induced amnesia by M. Vaj indicated the possible facilitation of cholinergic transmission or GABA benzodiazepine pathway. GC-MS of M. Vaj led to the identification of 141 compounds. α-asarone (72.12%) and β-asarone (72.12%) were found in the highest amount as compared to other compounds.